The Correlation Between Nursing Knowledge Of Surgical Wound Infections And The Method Of Surgical Wound Infection Prevention In Inpatient Ward Of Prima Husada Hospital - Ana, Karisma Dwi; Wulansari, Heni Indra (Journal of Global Research in Public Health, 2019)
(SWI) Surgical Wound Infection is an infection that often occurs in patients after surgery. Most of Surgical Wound Infection comes from the pathogen endogenous flora of the patient's skin, mucous membranes. In addition there are exogenous Suber from the operating area. In this case the knowledge of nurses in Inpatient Installation greatly influences the method of nurse in prevention of the Surgical Wound Infection. The design of this study is a correlation study. The populations were nurses at the Inpatient Installation of Prima Husada Hospital, with inclusion and exclusion criteria by using purposive sampling technique. The results of research on nurses 'knowledge of the Surgical Wound Infection were not good; 19 respondents (45.2%) and nurses’ method on prevention of Surgical Wound Infection was not good; 20 respondents (47.6%). The results of normality test data with Chi square test can be known that (p) obtained is 0,000 (p <0.05). The obtained data is normal data. The results of correlation test using the Pearson Correlation between nurses 'knowledge of the SWI and SWI Prevention method in the Inpatient Installation of Prima Husada Hospital can be found that (p) obtained on nurses' knowledge is 0.023, and on nurse method is 0.023 (p <0.05) . It mean there is a correlation between nurses' knowledge of the Surgical Wound Infection and Surgical Wound Infection preventive method at the Prima Husada Hospital Inpatient Installation. The statistical correlation can be said that the better the knowledge of nurses and the better the prevention method of the Surgical Wound Infection. This result will reduce the number of Surgical Wound Infection. .